EVALUATION BAROPODOMETRIC IN OBESE (Fiep Bulletin - online, 2014)
Introduction: Obesity is considered a disease of the group of chronic non communicable diseases, and various influencing factors in eating behavior, such as external factors related to the family and their characteristics, attitudes of parents and friends, social and cultural values, media, fast food, knowledge of nutrition and food fads, but also internal factors such as psychological needs and characteristics, body image, values ??and personal experiences, self-esteem, food preferences, health and psychological development. The consequences of the development of obesity are numerous and among them are mainly postural changes, knees and feet, there may be changes in body balance. Objective: To evaluate baropodometry through the changes that occur in the musculoskeletal system of obese individuals, analyzing the pressures podais in different regions of the plantar surface and compared with individuals who do not exhibit obesity. Methods: We evaluated 20 obese subjects, 15 women and 5 men, aged between 28 and 69 years and their controls, with 20 subjects matched for age and gender, and participants remained under platform baropodometry, real estate in bipedal posture for measurement of the load in plantar forefoot and hindfoot; plant load left and right, left and right mean pressure and contact surface. Results: With this study we found that people who are obese have a higher discharge plant in rearfoot when compared with the control group, weight bearing on the left side for both groups , average contact pressure higher than the control group; contact surface relatively close, with no significant differences from normality. Conclusion: we found that obese individuals compared to normal subjects, exhibit alterations in discharge plant in hindfoot and higher average pressure and contact, so further studies are needed to prove the changes podais related changes in the musculoskeletal system of these individuals.
Keywords: Obesity; Baropodometry; Alterations.